The culture of statistical data in support of social and economic change: the experience of collaboration between ISTAT and the National Third Sector Forum - Viviano, Lorena; Declich, Carlo; Novarino, Massimo; Bertoni, Patrizia; Giannelli, Mauro (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Italian National Institute of Statistics and the National Forum of the Third Sector are collaborating on a project to promote statistical culture for socially useful territorial action. The course focuses on the use of official statistical data and has an articulation of asynchronous and synchronous training moments. A subjective evaluation by the learners on the improvement of skills and professional growth is foreseen. The new competences make it possible to act in a context of profound economic and social change.